An Arts-Based Instructional Model for Student Creativity in Engineering Design - Laduca, Brian; Ausdenmoore, Adrienne; Katz-Buonincontro, Jen; Hallinan, Kevin Patrick; Marshall, Karlos (International Journal of Engineering Pedagogy (iJEP), 2017)
Over the past twenty years, nearly all job growth in the United States has emerged from new companies and organizations with assumedly innovative products, services, and practices. Yet, the nurturing of student creative thinking and problem solving is infrequent in engineering education. Inherent to developing these creativity skills and attributes is the need to be exposed to difference — in people and environment. Engineering education rarely offers such opportunities. Additionally, engineering students are rarely presented opportunities to develop designs responding to real human problems. This paper puts forth a new instructional model to address these needs by utilizing arts processes and practices as catalysts for both creativity development in students and transdisciplinary collaboration on problems addressing deep human needs. This model is premised on the substantiated role of the arts in developing creativity and growing understanding of the human condition. This art-based instructional model was piloted as exploratory pedagogical research during the summers of 2015 and 2016 as a partnership between the Arts Nexus (IAN) and the School of Engineering at the University of Dayton. In each year, this program supported twelve student interns from engineering, business, science, the arts, and the humanities to develop innovative technologies and services meeting client needs. Student growth in creative problem-solving and transdisciplinary collaboration, as well as the success of the completed innovation technology prototype were assessed by the project mentors and participating students via survey evaluations and narrative responses. The assessment results revealed substantial student growth in student creativity and transdisciplinary collaboration and a remarkably strong evaluation of the success of the students’ innovations. Also realized for all students was a transformation in their perception of their place in the world as professionals post-graduation.